Hemodialysis decreases carotid‐brachial and carotid‐femoral pulse wave velocities: A 5‐year follow‐up study. Issue 3 (3rd February 2015) - Cabrera Fischer, Edmundo I.; Bia, Daniel; Galli, Cintia; Valtuille, Rodolfo; Zócalo, Yanina; Wray, Sandra; Armentano, Ricardo L.
Abstract Aortic stiffness is a prognostic parameter associated with patient mortality. Vascular access creation has been shown to have effects on arterial stiffness both in the aorta and in the upper limb arteries in chronically hemodialyzed patients (CHPs). However, no longitudinal studies have been conducted in order to characterize the evolution of arterial stiffness in CHPs. The aims of this work were (a) to measure baseline pulse wave velocity (PWV) in the carotid‐femoral and in right and left carotid‐brachial pathways in a cohort of CHP and (b) to conduct a 5‐year prospective study on the same cohort to determine possible time‐related differences. Pulse wave velocity was measured both in the carotid‐femoral and in the carotid‐brachial pathways, and clinical and biochemical parameters were collected in 25 CHPs, which were followed up after a 5‐year lapse. Right and left carotid‐brachial pathway PWV values showed significant decreases after the 5‐year follow‐up, independently of the presence of the vascular access (P < 0.001). Additionally, baseline carotid‐brachial PWV was significantly higher (P < 0.001) than values measured 5 years later for upper limbs with vascular access (11.97 ± 2.97 m/sec vs. 6.76 ± 1.48 m/sec, respectively) and without vascular access (12.25 ± 2.38 m/sec vs. 7.18 ± 1.88 m/sec, respectively). Similarly, PWV values in the carotid‐femoral pathway decreased significantly (P < 0.001) over the same period (13.27 ± 2.96 m/sec vs. 9.75 ± 2.99 m/sec, respectively). The 5‐year follow‐up of PWV showed significant decreases in both carotid‐brachial and carotid‐femoral pathways. The general changes in arterial stiffness could be related to the vascular access creation, hemodialysis therapy, and to the improvement of arterial pressure management.